Fecal microbiota transplantation (FMT) for C. difficile infection, just say 'No'. (December 2019) - Tan, Xing; Johnson, Stuart
Abstract: Despite lack of regulatory approval, fecal microbiota transplantation (FMT) is widely performed to manage C. difficile infection (CDI), particularly recurrent CDI. Herein, we critically review the available randomized controlled trials of FMT and address the following questions: Is FMT better than drug management of recurrent CDI?; Is FMT treatment per se or adjunctive treatment to antibiotics for CDI?; and, Is FMT safe? Finally, we elaborate non-FMT options for the management of recurrent CDI. Although promising, FMT should be reserved for patients who have failed appropriate antibiotic management of recurrent CDI. Highlights: Randomized controlled trials of FMT for CDI have significant limitations. The relative efficacy of FMT compared to drug treatment may be closer than reported. Long term safety of FMT is unknown. Appropriate drug treatments should be used before considering FMT for recurrent CDI.